Exponential Stability for Nonlinear Perturbed Time Scales Systems with Gr"onwall-Bihari-Inequalities - Ayari, Amira; Boukerrioua, Khaled; Kilani, Brahim (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper focuses on the problem of exponential stability of certain classes of dynamic perturbed systems on time scales using time scale versions of some Grönwall-Bihari type inequalities.We prove under certain conditions on the nonlinear perturbations that the resulting perturbed nonlinear initial value problem still acquire exponential stable, if the associated linear system has already owned this property. The paper ends up with two illustrative examples to highlight the utility of our results.